Development and Validation of HPTLC Method for Simultaneous Estimation of Emtricitabine, Rilpivirine and Tenofovir Disoproxil Fumarate in Combined Dosage form (Bangladesh Pharmaceutical Journal, 2016)
This study describes the development and validation of high performance thin layer chromatographic (HPTLC) method for the simultaneous estimation of Emtricitabine (EMT), Rilpivirine (RPV) and Tenofovir disoproxil fumarate (TFV) in combined dosage form. Chromatographic separation of these drugs was performed on aluminum plates precoated with silica gel 60 F254 as the stationary phase using solvent system consisted of chloroform: ethyl acetate: methanol: glacial acetic acid (5:2:1:0.1 v/v/v/v). The densitometric analysis was carried out in absorbance mode at 272 nm. The drugs were satisfactorily resolved with Rf values of 0.28 ± 0.02, 0.70 ± 0.02 and 0.52 ± 0.04, respectively. The method was validated according to the International Conference of Harmonization (ICH) guidelines. The calibration curves were linear over the (r2 > 0.999) concentrations range from 600-2400 ng band-1 for Emtricitabine, 50-300 ng bands-1 for Rilpivirine and 600-3600 ng band-1 for Tenofovir disoproxil fumarate. The method showed accuracy of 100.01%, 100.32% and 100.14% and percentage assay of 99.91%, 98.72% and 99.34% for Emtricitabine, Rilpivirine and Tenofovir disoproxil fumarate, respectively. Percentage relative standard deviation (